A Deep Dive into Institutional and Economic Influences on Poverty in Europe - Dorin Jula; Lavinia Mastac; Diane Paula Corina Vancea; Kamer-Ainur Aivaz (Risks, 2025)
This study analyzed the evolution of the poverty rate between 2004 and 2023 in 29 European countries, using two categories of variables: institutional variables (Corruption Control Index and Rule of Law Index) and economic variables (unemployment rate, shadow economy, government expenditures on social protection and the Gini index). The methodology adopted included dynamic panel econometric models, applying a technique which involves the elimination of individual effects by a primary differencing of the variables and the use of the generalized method of moments (GMM) to evaluate the estimators. This methodology eliminates endogeneity caused by including the dependent variable with lag among the explanatory variables in the model. The results showed a strong negative correlation between the poverty rate and institutional variables, suggesting that improvements in governance and access to education and health resources are essential for poverty reduction. The shadow economy has also been identified as a poverty buffer, providing support in the absence of formal employment opportunities. The short-term impact of government expenditures on social protection was not significant, indicating the need for further analysis to better understand these dynamics. This research can make a significant contribution to the design of more effective public policies aimed at reducing shocks, reducing inequality and promoting sustainable economic growth.